Solution of Fractional Kinetic Equations Involving Laguerre Polynomials via Sumudu Transform - Wagdi F. S. Ahmed; D. D. Pawar; W. D. Patil (Journal of Function Spaces)
This study focuses on calculating solutions for fractional kinetic equations involving Laguerre polynomials and their fractional derivatives. By leveraging the Sumudu transform technique, we derive these solutions in the form of the Mittag-Leffler function. Our investigation includes graphical representations generated using MATLAB to illustrate the behavior of these solutions under varying parametric conditions. It is essential to note that the results obtained in this study are exceptionally versatile and have the potential to yield both established and potentially novel findings in this field of research.